2000
DOI: 10.1161/01.cir.101.19.2271
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on Cardiac Structure and Function

Abstract: Non-insulin-dependent DM has independent adverse cardiac effects, including increased LV mass and wall thicknesses, reduced LV systolic chamber and myocardial function, and increased arterial stiffness. These findings identify adverse cardiovascular effects of DM, independent of associated increases in BMI and arterial pressure, that may contribute to cardiovascular events in diabetic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
525
5
16

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 833 publications
(597 citation statements)
references
References 33 publications
51
525
5
16
Order By: Relevance
“…2,5,9 Non-insulin-dependent diabetes mellitus has been independently associated with an increase in left ventricular mass. 33,34 In our previous study among DHCCP patients, blood glucose concentration tended to be inversely related to the presence of ECG LVH by Sokolow-Lyon criterion. 35 In the Framingham Heart Study after adjusting for BMI and other risk factors, severity of hyperglycaemia was observed to be related to left ventricular mass more strongly in women than in men.…”
Section: Discussionmentioning
confidence: 85%
“…2,5,9 Non-insulin-dependent diabetes mellitus has been independently associated with an increase in left ventricular mass. 33,34 In our previous study among DHCCP patients, blood glucose concentration tended to be inversely related to the presence of ECG LVH by Sokolow-Lyon criterion. 35 In the Framingham Heart Study after adjusting for BMI and other risk factors, severity of hyperglycaemia was observed to be related to left ventricular mass more strongly in women than in men.…”
Section: Discussionmentioning
confidence: 85%
“…4,5 Arterial stiffening occurs as a consequence of aging and is increased in the presence of risk factors for atherosclerosis such as hypertension, diabetes mellitus, hypercholesterolemia and smoking. [6][7][8] There is evidence suggesting that aortic pulse wave velocity (PWV) and wave reflections as assessed by augmentation index (AIx) are associated with an increased risk of cardiovascular disease in young and middle-aged men. 9 PWV and AIx have been found to be elevated in patients with active arteritis.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Moreover, diabetes has a negative impact on treatment-induced changes in LV structure and function in hypertensives with LVH. 29 In the Strong Heart Study, 27 which involved a wide group of American Indians, diabetic subjects had higher LVM, interventricular septum thickness, PWT and RWT in comparison with subjects without diabetes, with no difference in LV chamber size.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Moreover, diabetes has a negative impact on treatment-induced changes in LV structure and function in hypertensives with LVH. 29 In the Strong Heart Study, 27 which involved a wide group of American Indians, diabetic subjects had higher LVM, interventricular septum thickness, PWT and RWT in comparison with subjects without diabetes, with no difference in LV chamber size. Similar results were obtained in the HYperGEN Study, 28 in which diabetic hypertensives had higher LVM and more concentric geometry when compared with non-diabetic hypertensives (again in this study diabetics had higher LVM, interventricular septum thickness, PWT and RWT but there was no difference with regard to LV diameter).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation